Digital Leadership and Employee Performance: Mediating Role of Digital Culture and Digital Skill in Financial Services Companies in Jakarta - Shinta Arista; Muhammad Ramaditya; Abdul Razak Abdul Hadi (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Digital Transformation Landscape in Indonesia asserts that successful digital transformation in Indonesia depends not only on technology adoption but also on human resource readiness and leadership effectiveness in guiding change processes.Purpose: This study aims to analyze the influence of digital leadership on employee performance, with digital culture and digital skills serving as mediating variables, among employees working in financial services companies in Jakarta, including the banking, securities, investment, insurance, and financing sectors. Design/methodology/approach: The research employs a quantitative approach by distributing questionnaires to 124 respondents and analyzing the data using Structural Equation Modeling (SEM). The study used non-probability purposive sampling due to limited population accessibility and specific criteria for respondents, namely employees who have worked in the company for at least one year and utilize digital technology in their daily tasks.Findings/Result: The findings indicate that digital leadership has a positive and significant effect on employee performance, both directly and through the mediation of digital culture and digital skills. Conclusion: These results conclude that strong digital leadership enhances employees’ digital skills, fosters a digital culture, and improves employee performance, thereby supporting the company’s digital transformation initiatives, while also extending the literature on their mediating roles in digital transformation contexts.Originality/value (State of the art): A well-established digital culture encourages employees to view digital technology not merely as a tool but as an integral part of daily work practices. The internalization of digital-based values, norms, and habits enables employees to leverage technology for faster, more integrated information sharing, collaboration, and innovation. Keywords:  digital leadership, digital culture, digital skill, employee performance, financial services industry